Dose-effect relationship between vaginal dose points and vaginal stenosis in cervical cancer: An EMBRACE-I sub-study. (March 2022) - Westerveld, Henrike; Kirchheiner, Kathrin; Nout, Remi A.; Tanderup, Kari; Lindegaard, Jacob C.; Spampinato, Sofia; Sturdza, Alina; Nesvacil, Nicole; Bruheim, Kjersti; Hellebust, Taran P.; Pieters, Bradley R.; Kirisits, Christian; et al.
Highlights: Doses to the vaginal dose points predicts well the risk of vaginal morbidity. Higher doses to the vaginal PIBS points are associated with vaginal stenosis. A shorter vaginal reference length is associated with ≥grade 2 vaginal stenosis. Abstract: Background and purpose: To evaluate dose–effect relationships between vaginal dose points and vaginal stenosis in patients treated for locally advanced cervical cancer with radio(chemo)therapy and image-guided adaptive brachytherapy. Material and methods: Patients from six centres participating in the EMBRACE-I study were included. Information on doses to different vaginal dose points, including the Posterior-Inferior Border of Symphysis (PIBS) points and recto-vaginal reference (RV-RP) point, were retrieved from the treatment planning system. In addition, the vaginal reference length (VRL) was evaluated. Vaginal stenosis was prospectively assessed according to the CTCAEv3.0 system at baseline and follow-up. Primary endpoint was grade 2 or higher (G ≥ 2) vaginal stenosis. Impact of dose to the vaginal dose points, and impact of VRL, age, vaginal involvement and applicator on vaginal stenosis G ≥ 2 was evaluated with a Cox proportional-hazard regression model. Results: 301 patients were included. Median follow-up was 49 months. During follow-up, the incidence of G0, G1, G2, and G3 vaginal stenosis was 25% (76), 52% (158), 20% (59) and 3% (8), respectively. Median total doses to PIBS+2 cm, PIBS, PIBS-2 cm and the RV-RP were 52.9 (IQR 49.3–64.7), 41.0 (IQR 15.4–49.0), 4.1 (IQR 2.9–7.0) and 64.6 (IQR 60.0–70.6) Gy EQD23, respectively. Higher doses to the PIBS, PIBS + 2 cm and RV-RP points were significantly associated with increased risk for vaginal stenosis G ≥ 2. Other risk factors for vaginal stenosis were: vaginal involvement at diagnosis, higher age, shorter VRL and use of a tandem-ovoid applicator. Conclusion: Higher doses to the PIBS+2 cm, PIBS and RV-RP dose points are associated with vaginal stenosis G ≥ 2.